Influence of Profitability, Capital Structure, Liquidity and the Size of the Company to the Quality of Profits - Reska Prahasini Sekarwesma; Mutiara Ilmiana Nur Isfani (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2025)
Purpose – penelitian ini membahas Earnings Quality dan faktor lainnya seperti Profitabilitas, Struktur Modal, Likuiditas dan Ukuran Perusahaan yang berfokus pada perusahaan sektor basic material. Penelitian ini menggunakan Modified Jones model sebagai pengukuran dari Kualitas Laba. This study aims to test and analyze the effect of Profitability, capital Structure, Liquidity and company Size on earnings Quality. Design/methodology/approach – The population in this study used basic material companies listed on the Indonesia Stock Exchange (IDX) in 2017-2022. This type of research is quantitative research. The data collection technique used in this study used the purposive sampling method and obtained a total of 12 companies. The analysis method used is multiple linear regression analysis using Eviews 9 software. Findings – The results of this study indicate that the Profitability variabel has a negative and statictically significant effect on earnings quality, the Capital Structure variabel has a negative and statistically insignificant effect on earnings quality, the Profitability variabel has a positive and statistically insignificant effect on earnings quality, and the Firm Size variabel has a positive and statictically insignificant effect on earnings quality.